2023
DOI: 10.31580/jrp.v4i2.2702
|View full text |Cite
|
Sign up to set email alerts
|

Peer Pressure, Academic Stress and Goal Adjustment in Day Scholars and Hostelite College Students

Abstract: The current study aimed to investigate the gender differences in peer pressure, academic stress, and goal adjustment in day scholars and hostelite college students. A cross-sectional survey research design and convenience sampling strategy were used. Data were collected from 300 college students (day scholars = 171 and hostelites = 129) with a mean age of 17.26(0.86) years of day scholars and a mean age of 17.57(0.91) of hostelites from various public and private colleges, Lahore. For this purpose, Peer Pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Gs et al (2021) explored the relationship between student alienation and organizational culture in an educational institution, indicating the potential negative effects of peer pressure on students' well-being and academic success. Maqsood et al (2022) and other similar studies support the notion that peer pressure negatively impacts academic performance. Laidee Dianne Dayanap and Marilou Y. Limpot (2023) found that peer pressure reduces students' motivation, but cooperative learning mitigates this negative effect.…”
supporting
confidence: 62%
“…Gs et al (2021) explored the relationship between student alienation and organizational culture in an educational institution, indicating the potential negative effects of peer pressure on students' well-being and academic success. Maqsood et al (2022) and other similar studies support the notion that peer pressure negatively impacts academic performance. Laidee Dianne Dayanap and Marilou Y. Limpot (2023) found that peer pressure reduces students' motivation, but cooperative learning mitigates this negative effect.…”
supporting
confidence: 62%
“…Many previous studies supported our findings (SARI & TEKBIYIK, 2012). According to Maqsood et al (2022), male students may be more vulnerable to peer pressure because they spend more time with their friends and have more outside environmental exposure than female students.…”
Section: Discussionmentioning
confidence: 99%